To Be Immortal, Do Good or Evil. (June 2018) - Gray, Kurt; Anderson, Stephen; Doyle, Cameron M.; Hester, Neil; Schmitt, Peter; Vonasch, Andrew J.; Allison, Scott T.; Jackson, Joshua C.
Many people believe in immortality, but who is perceived to live on and how exactly do they live on? Seven studies reveal that good- and evil-doers are perceived to possess more immortality—albeit different kinds. Good-doers have "transcendent" immortality, with their souls persisting beyond space and time; evil-doers have "trapped" immortality, with their souls persisting on Earth, bound to a physical location. Studies 1 to 4 reveal bidirectional links between perceptions of morality and type of immortality. Studies 5 to 7 reveal how these links explain paranormal perceptions. People generally tie paranormal events to evil spirits (Study 5), but this depends upon location: Evil spirits are perceived to haunt houses and dense forests, whereas good spirits are perceived in expansive locations such as mountaintops (Study 6). However, even good spirits may be seen as trapped on Earth given extenuating circumstances (Study 7). Materials include a scale for measuring trapped and transcendent immorality.